2020
DOI: 10.1186/s12937-020-00543-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in dietary intake across the lifespan: the case of Lebanon

Abstract: Background:Little is known about sex-based dietary differences in middle-income countries, particularly those undergoing the nutrition transition. This study aims at examining sex disparities in energy and macronutrients' intakes, food consumption patterns, and micronutrients' adequacy in Lebanon, while adopting a life course approach. Methods: Data were derived from a national cross-sectional survey conducted in Lebanon in 2008/2009. The study sample consisted of 3636 subjects: 956 children and adolescents ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 53 publications
3
30
1
Order By: Relevance
“…This study reported girls were significantly more likely to consume fast food compared with boys. The finding of this study contradicts with other studies [19,20]. A previous study found that adolescent girls were more likely to visit fastfood outlets in special days to meet with friends or family than boys especially in city centres [21].…”
Section: Discussioncontrasting
confidence: 99%
“…This study reported girls were significantly more likely to consume fast food compared with boys. The finding of this study contradicts with other studies [19,20]. A previous study found that adolescent girls were more likely to visit fastfood outlets in special days to meet with friends or family than boys especially in city centres [21].…”
Section: Discussioncontrasting
confidence: 99%
“…As a result, it is not surprising that a widespread inadequate dietary intake of the abovementioned vitamins and minerals was simultaneously observed in the diet of the mothers in our survey. Our findings corroborate with those of Nasreddine et al showing that Lebanese women had a high intake of total fat and higher consumption of sweets, while a lower micronutrient intake was observed [ 18 ]. We suggest that similar dietary patterns, that mimic those of the local population, were a sign of “dietary acculturation”.…”
Section: Discussionsupporting
confidence: 92%
“…The Eastern Mediterranean Region has been witnessing rapid changes in food consumption habits coupled with a high burden of micronutrient deficiencies, increasing obesity rates, and a persistent burden of undernutrition. Women and girls are particularly prone to various forms of malnutrition in this region [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, members of bigger households are less likely to consume adequate F+V compared to members of smaller households. While several studies [49,[58][59][60][61] indicated that females are more inclined towards healthier diets than males, Table 4 suggests that this is not the case in South Africa, especially concerning vegetable consumption. The insignificant estimated coefficient of gender on the vegetable consumption models indicates that there were no significant differences in both the frequency of vegetables, and the likelihood of consuming the minimum recommended level, between female and male household heads.…”
Section: Resultsmentioning
confidence: 97%